KETAHANAN PANGAN PASCA PANDEMI: STRATEGI KOMUNIKASI SEBAGAI KATALISATOR INOVASI BISNIS DAN PEMASARAN PANGAN - Ginting, Magdalena Lestari; Sumampouw, Carly; Adikarjo, Christoper Patrick; Krisdianto, Hans (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2023)
Food is a source of energy to all living beings, as food gives energy through chemical changes that produce ATP (Adenosine Triphosphate) and ADP (Adenosine Diphosphate). Food energy comes in different types of reactions, there are 3 main types of sources of energy carbohydrates, protein, and fat. Meat is one of the main food that many people feed on. This common meat mostly contains mainly protein and fat. This activity is an early step to introduce the scope of performance allocated to companies that will later be appointed to accompany the development of both product and marketing innovation. The product innovations from this activity are revolutionizing the steak industry through dry-aging and home preparation, igniting the grill: innovating the steak experience through T-bone grilling, elevating the burger experience: a novel approach to grilled dry-aged burgers, rediscovering the versatility of top round: a proposal for promoting roasted top round, the sous vide revolution - a twist on traditional boneless beef short ribs, spicy hanger steak pizzaiola; and the marketing strategic communication innovation resulting from this activity is the culinary revival: reimagining recipes with food tech students.